¿Ahora qué?: Cultural Adaptation of a Cancer Survivorship Intervention for Latino/a Cancer Survivors. Issue 9 (16th July 2019) - Valle, Carmina G.; Padilla, Neda; Gellin, Mindy; Manning, Michelle; Reuland, Daniel S.; Rios, Peggy; Lane, Gema; Lewis, Virginia; Rosenstein, Donald L.
Abstract: Objective: With a steadily increasing number of Latino/a cancer survivors, there is a need for supportive care programs for this underserved survivor subgroup. Methods: In this study, the authors culturally adapted an evidence‐based survivorship program, Cancer Transitions: Moving Beyond Treatment (CT) for this population. Guided by Barrera and Castro's heuristic model for cultural adaptation of interventions, we conducted five focus groups (FG) among Latino/a cancer survivors (n = 54) in several US sites to inform the preliminary adaptation of program materials. We conducted four additional FGs (n = 38) to obtain feedback on adapted materials. Results: Common themes from initial FGs were related to program delivery and logistics, and general recommendations for CT modification. Program adaptations addressed information needs, including health care system navigation, employment concerns, and sexuality. Other adaptations included an emphasis on family, spirituality, culturally appropriate translation and features, and role plays. Participants in the second round of FGs confirmed adaptations incorporated earlier findings and suggested additional refinements. Conclusion: This project helps guide the cultural adaptation of survivorship programs for Latino/a cancer survivors.